Evaluasi Pembelajaran Berbasis Multikultural Untuk Mengembangkan Karakter Bangsa Di Sekolah Dasar Negeri Rawarengas 2 - Ina Magdalena; Shinta Anjani Nura; Tiara Nur Cahyani; Vadlina Putry Prikustini (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
SDN Rawarengas 2 is a school located in one of the areas in Tangerang Regency, precisely in Rawarengas Village. Learning is basically a process of interaction between educators and students, both direct (face-to-face) and indirect interaction (learning activities using learning media in web applications). Multicultural-based learning in elementary schools plays an important role in developing the nation's character that is inclusive and respects diversity. In this era of globalization, society is increasingly diverse with various cultural backgrounds, tribes, religions, and different traditions. Therefore, education that focuses on multiculturalism is important to prepare the younger generation to face the challenges and needs of an increasingly complex society. This study used an interview method to one of the teachers of SDN Rawarengas 2. The interview was conducted directly/offline by approaching the speakers.